Administrative Creativity and Its Role in Decision-Making among Elite League Handball Club Coaches from the Players’ Perspective - Abdullah Abdulmohsen Khalaf; Saadoun Qasim Lazim (Journal of Education and Sport Science, 2026)
Objectives: This study aimed to develop two scales for measuring administrative creativity and decision-making among coaches of Iraqi Elite Handball League clubs, identify their levels, and examine the role of administrative creativity in supporting coaches’ decision-making. Materials and Methods: This study used a descriptive survey design with a correlational approach. The population consisted of 196 players from Iraqi Elite Handball League clubs during the 2024–2025 season. The sample was divided into an exploratory sample of 14 players, a scale-construction sample of 112 players, and an application sample of 70 players. Two scales were developed: the Administrative Creativity Scale and the Decision-Making Scale. Validity was examined through expert judgment, item discrimination, and internal consistency, while reliability was assessed using Cronbach’s alpha. Data were analyzed using SPSS and Microsoft Excel. Results: The final Administrative Creativity Scale consisted of 80 items across seven domains, while the Decision-Making Scale consisted of 56 items across five domains. The administrative creativity level was moderate, with a mean score of 267.814, while the decision-making level was high, with a mean score of 203.85. Most coaches were perceived to have moderate administrative creativity and high decision-making ability. Conclusions: The two developed scales were valid and reliable for measuring administrative creativity and decision-making among elite handball coaches. Administrative creativity appears to support decision-making by helping coaches generate alternatives, adapt to match situations, and select appropriate solutions under competitive pressure.